PENGARUH POLA AKTIVITAS MASYARAKAT TERHADAP KONFIGURASI RUANG DENGAN PENDEKATAN SPACE SYNTAX DI PUSAT KOTA DENPASAR - I Kadek Galih Juni Artha; Wahyudi Arimbawa; I Nyoman Harry Juliarthana (UNHI PRESS, 2023)
This research aims to analyze the influence of community activity patterns on spatial configuration in the city of Denpasar. The dense urban condition and population growth and activities have led to an increasing need for space, hence strategic planning and design using spatial models are necessary to address various levels of built environment such as transportation, demographics, business, production, services, tourism, healthcare sector, lifestyle, and recreation. The research method used is qualitative and quantitative analysis with a descriptive and correlation approach. Respondents taken in this study are the community in Denpasar who have different activity patterns. The results show that community activity patterns significantly affect the spatial configuration in Denpasar, and topological and geometric grid analysis can help understand the city's spatial structure, potential, and impacts on social behavior and economic activities. There is a need for strategic planning and design that considers community activity patterns in the formation of spatial configuration in Denpasar to improve the quality of life and promote balanced and sustainable economic development.